"Collision" ethno-cultural civilizations as a problem of the philosophy of history - Харченко, С.П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The article analyzes the specific ethnic and cultural civilizations in the context of general civilization development processes and identify the consequences of their interaction.